Aspek Determinan Ibu Dalam Praktik ASI Eksklusif di Wilayah Kerja Puskesmas Kabupaten Karawang - Rahayu, Yayuk Sri (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Breast milk is the best food a mother can give to her baby. Only breast milk alone is enough to meet his needs until the baby is in the first 6 months. Exclusive breastfeeding for infants is highly recommended, without any other food or drink except drugs and vitamins. The purpose of this study was to determine the proportion and determinants of exclusive breastfeeding in the working area of the Karawang district health center. The research design used a cross-sectional study with 242 respondents. Data analysis used univariate analysis, bivariate analysis, and multivariate analysis. The results of the analysis show that the percentage of exclusive breastfeeding is still low, which is only 46.3%. Variables that have a significant relationship with exclusive breastfeeding are knowledge, exposure to formula milk, and age. Variables that have no significant relationship with exclusive breastfeeding are the level of education, attitudes, beliefs, and facilities. The most dominant variable related to exclusive breastfeeding was knowledge value (P = 0.002 OR = 384.048). There is a need for information dissemination, regarding the benefits, and good methods of exclusive breastfeeding through training, seminars, counseling, counseling, and the media.